PENDIDIKAN MULTIKULTURAL DAN RELEVANSINYA TERHADAP PENDIDIKAN ISLAM DI INDONESIA - ., Ida Nurjanah (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2018)
Education conditions in each country is different. This could be due to differences in ethnicity, language and culture. Therefore, it is necessary education that can accept such differences through multicultural education. Multicultural education in Indonesia itself has been discourse by education experts has long since. One of those educational figures is our National Father?s Education Ki Hadjar Dewantara, who has made concepts and thoughts about multicultural education. He is an expert in the world of education and many educational concepts in Indonesia today is referring to his thoughts. The pattern of educational thought is nationalist and universal. Nationalistic, because education based on the principle of national culture, while universal is education that can be accepted and enjoyed of every human, class, race, ethnic, nation, religion and culture. So from his thoughts are focused on the teachings of character, independence, humanity and culture of the nation (multicultural).